Evaluating the accuracy of geometrical distortion correction of magnetic resonance images for use in intracranial brain tumor radiotherapy - Bagherimofidi, Seyed Mehdi (Rep Pract Oncol Radiother, 2019)
AIM: Determine the 1) effectiveness of correction for gradient-non-linearity and susceptibility effects on both QUASAR GRID(3D) and CIRS phantoms; and 2) the magnitude and location of regions of residual distortion before and after correction. BACKGROUND: Using magnetic resonance imaging (MRI) as a primary dataset for radiotherapy planning requires correction for geometrical distortion and non-uniform intensity. MATERIALS AND METHODS: Phantom Study: MRI, computed tomography (CT) and cone beam CT images of QUASAR GRID(3D) and CIRS head phantoms were acquired. Patient Study: Ten patients were MRI-scanned for stereotactic radiosurgery treatment. Correction algorithm: Two magnitude and one phase difference image were acquired to create a field map. A MATLAB program was used to calculate geometrical distortion in the frequency encoding direction, and 3D interpolation was applied to resize it to match 3D T1-weighted magnetization-prepared rapid gradient-echo (MPRAGE) images. MPRAGE images were warped according to the interpolated field map in the frequency encoding direction. The corrected and uncorrected MRI images were fused, deformable registered, and a difference distortion map generated. RESULTS: Maximum deviation improvements: GRID(3D), 0.27 mm y-direction, 0.07 mm z-direction, 0.23 mm x-direction. CIRS, 0.34 mm, 0.1 mm and 0.09 mm at 20-, 40- and 60-mm diameters from the isocenter. Patient data show corrections from 0.2 to 1.2 mm, based on location. The most-distorted areas are around air cavities, e.g. sinuses. CONCLUSIONS: The phantom data show the validity of our fast distortion correction algorithm. Patient-specific data are acquired in <2 min and analyzed and available for planning in less than a minute.